Effects of organic compounds and recycling on ozone absorption in a portable water purification unit. Issue 1 (11th December 2007) - Yao, P. X.; Hendrawan, F. B.; Bi, H. T.; Wang, J. H.; Fu, J.
Abstract : The absorption of ozone gas in a portable bubbling unit was investigated. First, six types of bubblers were tested under identical operating conditions with a gas flow rate of 1 L/min and a water volume of 1.5 L. A simple mass transfer model with the liquid phase assumed to be completely mixed and the axial ozone gas concentration gradient neglected was used to obtain the overall mass transfer coefficient, K L a, by fitting experimental data. The effect of organic compounds in the water on ozone absorption and liquid ozone concentration buildup was investigated experimentally using phenol as a model compound. It was found that the existence of phenol significantly reduced the liquid ozone concentration because absorbed ozone is consumed for the destruction of phenol, leading to the delay in liquid phase ozone concentration buildup. The implication is that the disinfection time was prolonged when water of high organic compounds concentration is to be purified. Using the completely stirred tank reactor model, the gas recycling is simulated and demonstrated to be effective for enhancing ozone utilization efficiency in the small portable water purification unit.